Subjective Well-Being Siswa SMA Jurusan IPA dan IPS - Komang A. W. Mahayasih; Dian Lestari Anakaka; Fredericksen Victoranto Amseke (Universitas Nusa Cendana, 2020)
Subjective well-being is circumstances of prosperous and self-satisfaction, which is the positive satisfaction that happens if the need and hope of someone is being fulfilled. Subjective well-being is caused by positive effect, negative effect, and life satisfaction effect. The purpose of this research is to find out the difference of subjective well-being of eleventh grades students of science and social programs. The sampling technique of this research is purposive sampling with the number of samples are 147 students in SMA Negeri 3 Kupang. The method of data analysis is t-test analysis method. The result of this research showed that the difference of subjective well-being of eleventh grade students of science and social programs with coefficient contras of t-test is 0,000 with p < 0,05